EFFECT OF THE SERVICE QUALITY ON TUTORING CUSTOMER'S WORD OF MOUTH AND SATISFACTION IN MALANG CITY - Salim, Teresia Purnomo; Rahayu, Mintarti; Sudjatno, Sudjatno (Jurnal Aplikasi Manajemen, 2019)
The purpose of the study was to test and explain the effect of service quality on customer satisfaction and word of mouth customers, as well as the effect of service quality on customer word of mouth mediated by customer satisfaction tutoring in Malang. The study population was students at the three biggest tutorings in Malang City who would take part in preparation for college admission selection in 2016. The research sample was 69 people who were determined by purposive sampling. Data analysis techniques using Partial Least Square ( PLS). The results showed that service quality had a significant effect on customer satisfaction and influenced the word of mouth of customers. However, customer satisfaction is not proven to mediate the influence of service quality on word of mouth because customer satisfaction does not have a significant effect on word of mouth. The quality of services provided by non-formal education in Malang City must be improved because it will have an impact on the increasing level of customer satisfaction.